Results of retinotomy for retinal detachment with marked proliferative vitreoretinopathy (Ukrainian Journal of Ophthalmology, 2025)
Background: Indications for retinotomy, its procedure and efficacy are still a subject for study and discussions.Purpose: To examine the efficacy of relaxing circumferential and radial retinotomies for retinal detachment associated with marked proliferative vitreoretinopathy (PVR).Material and Methods: Twenty-seven patients (27 eyes) with retinal detachment associated with PVR were involved in the study. Eleven eyes (40%) had retinotomy of less than 90°, eight (30%), of 90° to 180°, four (15%), of 180° to 270°, and four (15%), 360° (circumferential retinotomy). Additional radial retinotomy was performed in 5 eyes (19%), and retinotomy combined with choroidectomy, in 2 eyes.Results: Of the 27 eyes, retinal reattachment was achieved after the first surgery in 20 eyes (74%), after re-surgery in 5 eyes (19%). Anatomical success was achieved after removal of silicone oil in 15 eyes (56%). By the time of analysis, silicone oil was not removed in 12 eyes (44%). Complete retinal re-attachment was achieved in 25 eyes (93%), and partial re-attachment, in 2 eyes (7%).Conclusion: Retinotomy should be performed in eyes with retinal detachment and contraction. Circumferential and radial retinotomies provide a relatively high rate of anatomical success of surgery.
Keywords: retinal detachment; proliferative vitreoretinopathy; closed vitrectomy; retinotomy; retinal re-attachment